2022
DOI: 10.21037/gs-22-116
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors of complications in reduction mammoplasty—analysis of three different pedicles

Abstract: Background: Reduction mammoplasty can be performed in several different techniques. Understanding the complication profile and risk factors in different reduction methods can help in choosing a technique, which serves the patient best. The authors present their experience of three different reduction techniques [superomedial pedicle (SMP), superior pedicle (SP) and inferior pedicle (IP)] with an emphasis on predictors of complications. Methods: A retrospective review of a prospectively maintained database of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This comorbidity factor could explain the delay. This delay is often observed in patients with risk factors, as described by Palvé 26 and Sachs 25 in their respective studies. Management of delayed skin closure consists of continuing local care with rigorous asepsis.…”
Section: Commentsmentioning
confidence: 70%
See 1 more Smart Citation
“…This comorbidity factor could explain the delay. This delay is often observed in patients with risk factors, as described by Palvé 26 and Sachs 25 in their respective studies. Management of delayed skin closure consists of continuing local care with rigorous asepsis.…”
Section: Commentsmentioning
confidence: 70%
“…Bilateral gigantomastia was the most common in our study (75%), most often associated with a fibroadenoma. Gaye 24 and Palvé 26 report in their respective studies a predominance of bilateral gigantomastia. The mean breast axis in our study is similar to that reported by Abozeid, 27 in a case series study with 12-month follow-up of the Mac Kissock reduction plasty revisited, who found a similar result, i.e.…”
Section: Commentsmentioning
confidence: 94%
“…12 However, the superomedial pedicle represents only one approach in reduction mammaplasty and involves differences in technique, outcomes, and prevalence when compared with other approaches, such as inferior and superior pedicles. [13][14][15] These potential differences motivate a further exploration of the application of absorbable dermal staples during wound closure. In addition, in a review of the literature, we did not find a charge analysis of the impact of the absorbable deep dermal stapler that has incorporated overall hospital charge and operating room charges, which are important metrics for patients when considering financial burden.…”
mentioning
confidence: 99%
“…A previous study provided evidence that absorbable dermal staple closures in breast reductions with superomedial pedicles were associated with equal improvements to quality of life and rate of postoperative complications when compared with dermal suture closures after reduction mammaplasty 12 . However, the superomedial pedicle represents only one approach in reduction mammaplasty and involves differences in technique, outcomes, and prevalence when compared with other approaches, such as inferior and superior pedicles 13–15 . These potential differences motivate a further exploration of the application of absorbable dermal staples during wound closure.…”
mentioning
confidence: 99%
“…In the current study Palve et al present a retrospective review of 760 patients including three different pedicles [superomedial (SMP): 477 patients (63%); superior (SP): 201 patients (26%), and inferior (IP): 82 patients (11%) combined with statistical risk factor analysis to emphasize predictors of complications, classified by Clavien-Dindo ( 5 , 6 )]. A total of 578 patients (76%) were bilateral, 182 (24%) unilateral.…”
mentioning
confidence: 99%